Green Synthesis of Fe3O4 Nanoparticles Using Pineapple Peel Extract For Adsorption of Rhodamine B - Kodarta, Wahyu; Sinaga, July Fitry; Pane, Reza Hotna Uli; Pasaribu, Martali Uli; Ichsan, Ahmad Farizt; Bemis, Restina (LPPM, Institut Teknologi Sepuluh Nopember, 2024)
AbstractThis research aims to develop an environmentally friendly method for the synthesis of Fe₃O₄ nanoparticles using Tangkit pineapple peel extract with iron sand from the Batanghari River, Jambi, as raw materials. FTIR analysis detected Fe-O metal oxide clusters at a wavenumber of 533 cm⁻¹, confirming the presence of Fe₃O₄. The XRD diffraction pattern according to ICSD reference data number 01-076-0956 shows the highest intensity peak at an angle of 2θ 30.17°; 35.47°; 57.18°; and 62.77° with an average crystal diameter of 19.99 nm. SEM showed irregular particle morphology, while particle size analysis revealed an average particle size of 198 nm. Magnetic properties test using VSM shows that the nanoparticles are superparamagnetic with a saturation magnetization (Ms) of 26.25 emu/g. In the Rhodamine B adsorption test, the highest efficiency was achieved at a mass of 100 mg with a value of 95.21%. The optimum adsorption time occurred at 75 minutes with an efficiency of 98.52%. These results indicate that Fe₃O₄ nanoparticles synthesized via the green synthesis method using Tangkit pineapple peel extract have high potential for application in processing textile dye waste.Keywords: green synthesis, Fe3O4 nanoparticles, bioreductor, environmentally friendly. adsorbent.AbstrakPenelitian ini bertujuan mengembangkan metode ramah lingkungan untuk sintesis nanopartikel Fe₃O₄ menggunakan ekstrak kulit nanas Tangkit dengan pasir besi Sungai Batanghari, Jambi, sebagai bahan baku. Analisis FTIR mendeteksi gugus logam oksida Fe-O pada bilangan gelombang 533 cm⁻¹, mengonfirmasi keberadaan Fe₃O₄. Pola difraksi XRD sesuai data referensi ICSD nomor 01-076-0956 menunjukkan puncak intensitas tertinggi pada sudut 2θ 30,17°; 35,47°; 57,18°; dan 62,77° dengan diameter kristal rata-rata kristal sebesar 19,99 nm. SEM menunjukkan morfologi partikel tidak beraturan, sedangkan analisis ukuran partikel mengungkapkan rata-rata ukuran partikel 141,83 nm. Uji sifat magnetik menggunakan VSM menunjukkan nanopartikel bersifat superparamagnetik dengan magnetisasi saturasi (Ms) sebesar 26,25 emu/g. Pada uji adsorpsi Rhodamin B, efisiensi tertinggi tercapai pada massa 100 mg dengan nilai 95,21%. Waktu adsorpsi optimum terjadi pada 75 menit dengan efisiensi sebesar 98,52%. Hasil ini menunjukkan bahwa nanopartikel Fe₃O₄ yang disintesis melalui metode green synthesis menggunakan ekstrak kulit nanas Tangkit berpotensi tinggi untuk aplikasi dalam pengolahan limbah pewarna tekstil.Kata kunci: green synthesis, nanopartikel Fe3O4, bioreduktor, ramah lingkungan, adsorben.